Animal rationality : later medieval theories, 1250-1350 - Oelze, Anselm (Investigating Medieval Philosophy Ser., 2018)
In Animal Rationality: Later Medieval Theories 1250-1350, Anselm Oelze offers the first comprehensive and systematic exploration of theories of animal rationality in the later Middle Ages. Traditionally, it was held that medieval thinkers ascribed rationality to humans while denying it to nonhuman animals. As Oelze shows, this narrative fails to capture the depth and diversity of the medieval debate. Although many thinkers, from Albert the Great to John Buridan, did indeed hold that nonhuman animals lack rational faculties, some granted them the ability to engage in certain rational processes such as judging, reasoning, or employing prudence. There is thus a whole spectrum of positions to be discovered, many of which show interesting parallels with contemporary theories of animal rationality.